Effect of current density on the composition of Zn-Ni alloy deposits and the characteristics of the trivalent chromium passive film on these deposits - Le Ba, Thang; Nam, Trương Thị; Le Duc, Bao; Nguyen, Thi Thanh Huong; Uong Van, Vy; Le Thao, Ly (Vietnam Journal of Science and Technology, 2025)
The aim of this research is to investigate the influence of the composition of zinc-nickel (Zn-Ni) alloy coatings on the color and properties of chromium (III) passive films, with a specific focus on their corrosion protection abilities. The composition, phase structure, and morphology of these coatings were analyzed using energy dispersive spectrometry, X-ray diffractometry, and scanning electron microscopy, respectively. Additionally, chronopotentiometry and potentiostatic methods were employed to analyze the possible causes of the composition and structure changes induced by deposition current density. The results showed that the zinc-nickel alloy of interest has a body centered cubic (bcc) lattice structure and has a chemical formula of Ni5Zn21. The Ni content of Zn-Ni coatings is  about 12÷15 %. Efficiency at current density of 1 A/dm2 is the highest at 94.1 %, efficiency at current density of 5 A/dm2 is the smallest at 74.67 %, plating particles with dimensions in the range of 0.01 ÷ 1µm. All of TCP films on the Zn-Ni alloys deposited at different current densities meet DIN EN ISO 19598: 2017-04 standards.